PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL MENGGUNAKAN MEDIA GAMBAR - Ananda, Raditya Fariz; Asran, Mastar; Syamsiati, Syamsiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research was the students’ participation in Ilmu Pengetahuan Sosial (IPS) subject at class VC SD Negeri 34 Pontianak Kota The purpose of this research was to find out the improvement of students’ participation in Ilmu Pengetahuan Sosial (IPS) subject by using pictures as media of teaching at class VC SD Negeri 34 Pontianak Kota The method of this research was descrptive method inform of Classroom Action Research (CAR). This research was done at SD Negeri 34 Pontianak kota which are consists of 35 students. Technique of collecting data in this research was observation technique with observation sheets as the tool. Technique of data analysis used in this research was average score and percentage. This research was conducted in two cycles. The results of the research were divided into three aspects. 1) Teacher’s ability to plan teaching learning process by using pictures as media of teaching on the first cycle was 3,18 at good category, improved 0,59 to 3,71 at excellent category on second cycle. 2) Teacher’s ability during teaching learning process by using pictures as media of teaching on the first cycle was 3,16 at good category , improved 0,810 3,67 which included into excellent category. 3) Students’ participation in teaching learning activity by using pictures as media of teaching on the first cycle was 71,42% with high category, improved 22,51% to 86,98% with very high category on second cycle. The data above shows that using pictures as media teaching was able to improved students’ participation in teaching learning activity at class VC SD Negeri 34 Pontianak KotaKeywords : Improvement, Activity, Pictures